State Compliance with International Trade Law - Muhammad Haidar Ali; Moh Karim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
International trade law is part of international law. Therefore, various imperfections or weaknesses of international law are also affected in the field of international trade law. This article will explain why the state in conducting international trade needs to comply with international trade law. This article argues that the reason for the states to obey international trade law is due to the belief that obedience will benefit the interests of the country itself. The next reason is that there are fundamental principles within the scope of international treaties, which are the source of law from international trade law, namely the principle of good faith. A state that is bound in the international trade agreement shall implement the provisions of the treaty by contents, soul, purpose, and purpose of the treaty itself, respecting the rights and obligations of each party.